Examining Students' Translation Quality in Subtitling for the Deaf and Hard of Hearing - Aminudin, Muhammad Fauzan; Hidayati, Anni Nurul (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2022)
The past decade has shown the rapid development of digital media. Subtitling as a result of audio-visual translation (AVT) becomes a crucial part because it has to be able to provide the best subtitles for deaf and hard of hearing people. This descriptive qualitative study aims to examine the quality of subtitling for deaf and hard of hearing (SDH) of a subtitled movie entitled â€œThe Three Little Pigsâ€ by the students of English faculty in Surakarta city, Indonesia. Three raters are invited to contribute to assessing the quality of the subtitle. Concerning deaf and hard of hearing, the rater for readability aspect comes from the deaf person willing to contribute to the study. The finding of 72 data revealed that the quality of subtitling was accurate (51), acceptable (62), and less readable subtitling (49). The result can be helpful as a way of gaining accessibility and spreading the information to the DHH viewers. As the pedagogical implication of future work on translation, it can be used as a consideration to achieve the readability aspect more significantly, specifically, DHH readers or viewers.